2006
DOI: 10.1002/hc.20279
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of bonding in P4 clusters

Abstract: Quantum-topological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
(45 reference statements)
2
7
0
Order By: Relevance
“…This conclusion is consistent with our earlier results [9], in particular, the data on 31 P NMR spectra, and the quantum-chemical calculations of the P 4 -C 6 H 6 system [10,11].…”
Section: Resultssupporting
confidence: 92%
“…This conclusion is consistent with our earlier results [9], in particular, the data on 31 P NMR spectra, and the quantum-chemical calculations of the P 4 -C 6 H 6 system [10,11].…”
Section: Resultssupporting
confidence: 92%
“…The angle at the BCP is 170 and the position of the basin (see Fig. 7) is quite close to the position of the BCP calculated by Tsirelson et al (2006). This lack of linearity is typical for the strained bonds, although the angle is more open than that calculated by Jones & Hohl (1990).…”
Section: Figurementioning
confidence: 65%
“…This is also the reason why the O atoms in P 4 O 6 deviate much more from the P-P line than the O atoms in the SiO 2 polymorphs. This feature has found support in the theoretical study of the topology of the electron density in P 4 clusters reported by Tsirelson et al (2006), in which the bonding-critical points (BCPs) are out of the line connecting two P nuclei. Instead, the bonding points should be located on bent lines mimicking the banana-like orbitals mentioned above.…”
Section: Figurementioning
confidence: 71%
“…The Bader atoms in molecules theory AIM argues that the properties of molecular charge distribution are summarized in terms of its critical points. The analysis of the bond critical points carried out by the AIM2000 program at the STO-3G level on tetrahedral P 4 @B 80 suggests that the bond critical point (BCP) of each B−P bond lies nearer to the cap boron atom. The B−P bonding is a mixture of an ionic and covalent bond since the electron density at BCP along the B−P bond shown in Figure lies in the range of intermediate interaction defined in refs and , characterized by an electron density 0.07 < ρ < 0.15, an absolute ratio of principal curvatures λ 1 /λ 3 < 0.20 with λ 1 < λ 2 < λ 3 , a positive Laplacian of electron density and a negative total electronic energy. The positive value of the Laplacian expresses that electrons are depleting at that BCP.…”
Section: Resultsmentioning
confidence: 95%